2013
DOI: 10.1111/cmi.12232
|View full text |Cite
|
Sign up to set email alerts
|

Circulating lethal toxin decreases the ability of neutrophils to respond toBacillus anthracis

Abstract: SummaryPolymorphonuclear leucocytes (PMNs) play a protective role during Bacillus anthracis infection. However, B. anthracis is able to subvert the PMN response effectively as evidenced by the high mortality rates of anthrax. One major virulence factor produced by B. anthracis, lethal toxin (LT), is necessary for dissemination in the BSL2 model of mouse infection. While human and mouse PMNs kill vegetative B. anthracis, short in vitro half-lives of PMNs have made it difficult to determine how or if LT alters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 60 publications
1
34
0
1
Order By: Relevance
“…Other in vivo studies have indicated that LT is capable of reducing chemotaxis to PMA mediated inflammation in the ear in mice models [184].…”
Section: Immunological Effectsmentioning
confidence: 97%
See 4 more Smart Citations
“…Other in vivo studies have indicated that LT is capable of reducing chemotaxis to PMA mediated inflammation in the ear in mice models [184].…”
Section: Immunological Effectsmentioning
confidence: 97%
“…Therefore, it stands to reason that a swift influx of neutrophils is necessary to contain an infection by B. anthracis. Neutrophils play a key role in clearing B. anthracis infection and the exotoxin is capable of abrogating their protective effects [183][184][185]. Further, early production of pro-inflammatory cytokines, such as IL-1β, can increase host survival mediated by neutrophils [186].…”
Section: Immunological Effectsmentioning
confidence: 99%
See 3 more Smart Citations